Western and Arabic Islamic Architecture Discourse - Akram Jassim Al-Akkam (Iraqi Journal of Architecture and Planning, 2009)
Many literatures concentrated on the issue of architecture discourse which identified by thespace of conceptual thought that has essential characteristics based on knowledge foundations anddistinctive historical, cultural, religious, and social dimensions. These literatures pointed to westemarchitecture discourse elements and Arabic Islamic architecture discourse and cultural,environmental and doctrinal reference, But these literatures didn't present clear comparative picturefor those discourses.The aim of current investigation is to conduct a comparison between those discourseelements, it hypothesized a variation between their structural foundations.To achieve the study aim, the research depended on intensive theoretical literature review.The results demonstrated, the variation of discourses at almost all elements which include,the view toward human existence in cosmos, the method of understanding of metaphysical world,the nature of human, reference ofdiscourse and its nature, discourse dependencies, objectives andcharacteristics, the mechanism of conceptual thought, discourse building and types, interest andconcentrating approaches, method of embodiment, research topics, the nature of viewing aestheticsand aesthetic values production methods and rules, spatial perception, viewing creating. architectureas a culture and its reference origins, contemporarization and originality, theory and practice,spatiality of evaluation criteri4 expression and meaning and their tools, spatial correlation andsurrounding behavior, and lastly the positively and negativity of discourse.They study concluded that westem discourse depends on ego and individual philosophy ofvariable references that standing on heterogeneity and deference's forces, and its inhabituationslike deoonstruction, unfamiliarity, nihilism, and the complexity and ambiguity characteristics. Thewestern discourse is influenced by fourth dimension, trying to maximize lormal aesthetic values byusing art and concreted images. The westem discourse is intemational, scientific, utopic, abstractedinductive, methodologist, and ideologist one.The Arabic Islamic architecture discourse is depending on gathering and fixedcomprehensive principles represented by culture, environment, doctrine origins, legislation,religious conceptual thoughts. The Arabic discourse depends on homogeneous and similarity forcesand its inhabituations of compactness, simplicity, unity, and harmonious elements, trying tomaximize spiritual forces.The Arabic Islamic discourse is speculative, critical and deductive one.To sun up this investigation the Arabic Islamic discourse is more stable, durable, andcomprehensive one. And stands in apposition on westem discourse.